Penerapan Supervisi Klinis Kepala Sekolah terhadap Peningkatan Kualitas Pembelajaran: Studi di SDN 02 Kebonagung - Miftah Maulidiah; Shobihatul Fitroh Noviyanti; Layyina Sajieda; Muhammad Nabit Ilmil Arif (Al-Kindi, 2026)
This study aims to analyze the implementation of principal clinical supervision in improving the quality of learning at SDN 02 Kebonagung. Clinical supervision is an important effort to assist teachers in improving the learning process through systematic guidance, observation, and follow-up activities. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal and teachers. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results showed that the clinical supervision conducted by the principal was able to improve the quality of learning through structured supervision planning, direct feedback, and evaluation of teachers’ learning processes. In addition, clinical supervision encouraged teachers to enhance their professional competence, creativity, and discipline in teaching. The obstacles found in the implementation of supervision included limited time and differences in teachers’ ability to accept guidance. Therefore, principal clinical supervision plays an important role in supporting the improvement of learning quality in elementary schools